a\A technique on novel based marching ants colonies clusters for operational big data sets - Sreenu, Konda; Boddu Raja Srinivasa Reddy, Dr (International Journal of Engineering and Technology, 2018)
Computer plays a key role in everywhere world. Data is growing along with the usage of computers. In everyday life we use computer for various purpose and store bulk of information. One or other way we want to retrieve data from the storage system. Retrieving bulk of data information is not a simple thing or it is magic show. Every user wants data in different forms like reports or output information. For doing all this exercises we require one process. Process is nothing but marching ants colonies. Data related databases and tables are collected, trivial data is selected from huge tables and databases, apply aggregate functions on data and output information or reports related to data. Paper focus on how efficiently we can use software for some extent on solving business related problems. Paper may not solve century yearâ€™s data but we can achieve something. When century years data it is better to go for data mining approach because it accumulates large time to solve such big problemsÂ